2003
DOI: 10.1074/jbc.m208888200
|View full text |Cite
|
Sign up to set email alerts
|

Usage of Tautomycetin, a Novel Inhibitor of Protein Phosphatase 1 (PP1), Reveals That PP1 Is a Positive Regulator of Raf-1 in Vivo

Abstract: Protein phosphatase type 1 (PP1), together with protein phosphatase 2A (PP2A), is a major eukaryotic serine/threonine protein phosphatase involved in regulation of numerous cell functions. Although the roles of PP2A have been studied extensively using okadaic acid, a well known inhibitor of PP2A, biological analysis of PP1 has remained restricted because of lack of a specific inhibitor. Recently we reported that tautomycetin (TC) is a highly specific inhibitor of PP1. To elucidate the biological effects of TC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 53 publications
(76 reference statements)
7
63
1
Order By: Relevance
“…Direct dephosphorylation of Thr-202/Tyr-204 of ERK is conducted by its dedicated phosphatases, such as striatal enriched phosphoprotein (56) and MKP-2 (11). However, consistent with the results presented here, both PP1 and PP2A are thought to indirectly regulate ERK (57,58).…”
Section: Phosphomimetic Substitution At Either Thr-292 or Thr-286 Difsupporting
confidence: 82%
“…Direct dephosphorylation of Thr-202/Tyr-204 of ERK is conducted by its dedicated phosphatases, such as striatal enriched phosphoprotein (56) and MKP-2 (11). However, consistent with the results presented here, both PP1 and PP2A are thought to indirectly regulate ERK (57,58).…”
Section: Phosphomimetic Substitution At Either Thr-292 or Thr-286 Difsupporting
confidence: 82%
“…ERKs are activated by phosphorylation of both conserved threonine and tyrosine residues and inactivated on dephosphorylation by specific phosphatases (15)(16)(17)(18)(19)(20). Serine-threonine PP2A can dephosphorylate MEKand ERK-family kinases in vitro (21,22). In this study, we also found that inhibition of PP2A clearly restored sphingosineinduced suppression of MEK and ERK.…”
Section: Discussionsupporting
confidence: 63%
“…Serine-threonine protein phosphatase 2A (PP2A) dephosphorylates MAPK/ERK kinase (MEK) and ERK family kinases in vitro (19). Moreover, inhibition of PP2A leads to the activation of MEK and ERK (21,22). Recent studies show that ERK activity is down-regulated by serine-threonine phosphatase during p38 MAPK activation induced by arsenite in NIH 3T3 fibroblasts (23).…”
Section: Introductionmentioning
confidence: 99%
“…Both of these phosphatases are inhibited by CA, whereas PP2A is more specifically inhibited by 100 nM OA, and PP1 is more specifically inhibited by tautomycin (TM) (Connor et al, 1999;Mitsuhashi et al, 2003;Chen et al, 2005). Calyculin A treatment of 5637 cells led to substantial increases in pAkt S473 levels, whereas okadaic acid and tautomycin had less dramatic effects ( Figure 4C).…”
Section: T J Wiles Et Almentioning
confidence: 99%